TCF/LEF factor earn their wings. - Clevers, H.; van de Wetering, M. (Trends in Genetics, 1997)
Factors of the TCF/LEF HMG domain family (TCFs) exist in vertebrates, Drosophila melanogaster and Caenorhabditis elegans. It has very recently become evident that TCFs interact with the vertebrate WNT effector beta-catenin to mediate axis formation in Xenopus. Likewise, Armadillo (the Drosophila ortholog of beta-catenin) is genetically upstream of a Drosophila TCF in the Wingless pathway. Upon Wingless/Wnt signaling, Armadillo/beta-catenin associate with nuclear TCFs and contribute a trans-activation domain to the resulting bipartite transcription factor. The cytoplasmic tumor-suppressor protein APC binds to beta-catenin causing its destruction. In APC-deficient colon carcinoma cells, beta-catenin accumulates and is constitutively complexed with TCF factors. In APC-positive colon carcinomas and melanomas, dominant mutations in beta-catenin render it indestructable, providing an alternative mechanism to activate transcription of TCF target genes inappropriately. So, transcriptional activation of TCF target genes by beta-catenin appears to be a central event in development and cellular transformation.